What Does One See When the Lights Come on? - Heisig, James W. (Bulletin of the Nanzan Institute for Religion & Culture, 2009)
The following brief essay appeared originally in Catalan as an appendage to Raquel Bouso’s recent book, El Zen (Barcelona: Fragmenta Editorial, 2008). It is reproduced here in the hope of refreshing, if only for a moment, the image of the Zen patrimony as a treasure for all religions.